2018
DOI: 10.3390/diseases6020044
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Dyslipidemia in Type 2 Diabetes: Recent Advances in Nonstatin Treatment

Abstract: Dyslipidemia is a major risk factor for cardiovascular disease (CVD), which is the leading cause of morbidity and mortality in type 2 diabetes (T2DM). Statins have played a crucial role in its management, but residual risk remains since many patients cannot achieve their desired low-density lipoprotein cholesterol (LDL-C) level and up to 20% of patients are statin-intolerant, experiencing adverse events perceived to be caused by statins, most commonly muscle symptoms. Recently, great advances have been made in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Both drugs have been evaluated in diverse populations, including diabetic patients, and have been proven to be safe and efficient for decreasing LDL-C concentrations in monotherapy or when given in combination with statins, with or without ezetimibe. 52,53 They have also been authorised as additional therapy for patients with ASCVD or familial hypercholesterolaemia who are taking the maximally tolerated dose of statins but who require a further reduction in their levels of LDL-C. 10 FOURIER 54 and ODYSSEY OUTCOMES 55 showed a reduced number of cardiovascular events after treatment with evolocumab and alirocumab, respectively, related to the degree of further LDL-C lowering. While neither investigated a decrease in cardiovascular death, alirocumab, but not evolocumab, showed a decreased risk of all-cause death.…”
Section: New Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both drugs have been evaluated in diverse populations, including diabetic patients, and have been proven to be safe and efficient for decreasing LDL-C concentrations in monotherapy or when given in combination with statins, with or without ezetimibe. 52,53 They have also been authorised as additional therapy for patients with ASCVD or familial hypercholesterolaemia who are taking the maximally tolerated dose of statins but who require a further reduction in their levels of LDL-C. 10 FOURIER 54 and ODYSSEY OUTCOMES 55 showed a reduced number of cardiovascular events after treatment with evolocumab and alirocumab, respectively, related to the degree of further LDL-C lowering. While neither investigated a decrease in cardiovascular death, alirocumab, but not evolocumab, showed a decreased risk of all-cause death.…”
Section: New Treatmentsmentioning
confidence: 99%
“…have shown a dose-dependent relationship with risk of new-onset diabetes and, moreover, mendelian randomisation studies with genetic variants in PCSK9 have shown an increased risk of diabetes; 53 however, the clinical trials with PCSK9 inhibitors have not shown a higher incidence of diabetes or metabolic worsening in diabetic patients. 53,56 PCSK9 inhibitors have proven to be powerful LDL-C-lowering agents; however, the need for long-term safety studies and the high associated costs are the main challenges. 10,53 Possible Future Treatments An intracellular PCSK9 inhibitor, inclisiran, is currently in development for diabetes; its main differences from other PCSK9 inhibitors are the intracellular inhibition of mRNA and administration only twice a year.…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…European Guidelines on CVD prevention list the following statistically significant factors for the development of fatal CVD: gender, age, cholesterol level, blood pressure, and smoking status 19 . At the same time, DM is associated not only with hypercholesterolemia, but also with other lipid metabolism disorders such as dyslipidemia 20,21 , found in 72%-85% of patients with T2DM 22 . Dyslipidemia is defined as an abnormal lipid profile characterized by high total cholesterol (TC), high low-density lipoprotein cholesterol (LDL-C), low high-density lipoprotein cholesterol (HDL-C) and high triglycerides (TG).…”
Section: Introductionmentioning
confidence: 99%
“…The authors wish to make the following changes to their paper [ 1 ]. In Table 1, in the last row, the authors reported rates of Neutralizing antibodies: 42% vs. 6% in ODYSSEY Outcomes.…”
mentioning
confidence: 99%